Governing through uncertainty: 'refugeenes' in Turkey - Öztuzcu, Kristen Sarah Biehl. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
The basic objective of this thesis is to explore the meaning of ‘refugeeness’ in Turkey. First I examine the globalized discursive and institutional mechanisms, which have led to the production of a universalized and standardized ‘refugee’ identity that has come to be characterized as a condition of homelessness, statelessness and loss of identity. Such discursive constructions, it is argued, have a powerful effect, serving both as an essential tool for the normalization of territorialized nation-state belonging and depoliticizing and de-contextualizing the causes and experiences of human displacement. However, based on my field research in Turkey, I argue that uncertainty is also a constitutive element of ‘refugeeness.’ The detailed mechanisms set in place to determine refugee status, and the highly restrictive asylum policies of the Turkish state justified by ‘security’ concerns, situates refugees in an extremely unstable and uncertain predicament. This ‘mood of precariousness’ invading the everyday lives of refugees in Turkey, also has a powerful governing effect. Refugees arriving in Turkey are contained and de-mobilized through uncertainty and indefinite waiting, which in turn, can serve as a psychological deterrence mechanism against seeking ‘legal’ asylum.
Keywords: Refugees -- Turkey.; Asylum, Right of -- Turkey.; Emigration and immigration -- Turkey.